Doppler Ultrasound Diagnostics in Thyroid Diseases - Xalilov, Izzatillo (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis highlights the importance of Doppler ultrasound examination in the diagnosis of thyroid diseases. The capabilities of Color Doppler and Power Doppler methods in assessing blood flow within the thyroid gland are analyzed. Particular attention is paid to Doppler findings observed in diffuse toxic goiter, thyroiditis, and nodular lesions. In addition, the diagnostic significance of vascularization characteristics and hemodynamic indicators in the differential diagnosis of benign and malignant nodules is discussed.